Tinjauan Yuridis Perjanjian Sewa Menyewa Tanah Untuk Usaha Rumah Makan Antara Pemerintah Daerah Kabupaten Sikka Dan Pengusaha Rumah Makan Di Kecamatan Alok Timur Kabupaten Sikka - Dua Tatu, Yohana Lidya Ayu Putri Yuliana; Nubatonis, Orpa J; Pello, Helsina F (Artemis Law Journal, 2025)
This study focuses on the legal analysis of land lease agreements for restaurant businesses between the Sikka District Government and restaurant entrepreneurs in Alok Timur Subdistrict, driven by the increasing demand for strategic land in line with economic growth. The objective of this research is to understand the lease agreement procedures in place and to identify the obstacles encountered in their implementation. The methodology employed is empirical legal research with a case study approach, involving interviews and observations of the relevant parties. The findings indicate that the lease agreement procedures at Maumere Market comply with the requirements set forth in the Civil Code; however, significant obstacles exist, such as delays in rent payments by tenants and unilateral increases in rental fees by landlords without adequate notice. The conclusion of this study emphasizes the importance of transparency and communication between landlords and tenants to avoid conflicts, and it provides recommendations for market managers to conduct socialization regarding leasing kata procedures and to consider tenants' conditions in setting rental fees, in order to create a more conducive and sustainable business environment.